EFFECTIVENESS OF CHITOSAN AND HYDROXYAPATITE FROM CRAB (PORTUNUS PELAGICUS) SHELLS AS BONE GRAFT ON BMP-2 EXPRESSION IN SOCKET PRESERVATION - SETIAWATI, DIAN; OKTAWATI, SRI; GANI, ASDAR; IRAWATY, ARNI; SARI, UMMI SALMIAH (International Journal of Applied Pharmaceutics, 2025)
Objective: Socket preservation involves inserting graft material into the tooth socket to prevent alveolar bone resorption and sustain bone volume. Crab shells contain high protein, chitin, and calcium carbonate, making them a potential novel material for bone grafts. This study aims to evaluate the efficacy of chitosan and hydroxyapatite (HA) derived from small crab (Portunus pelagicus) shell waste on Bone Morphogenetic Protein (BMP)-2 expression during socket preservation procedures in experimental animals. Methods: Chitosan derived from crab shells is produced through demineralization, deproteinization, and deacetylation processes. HA is derived from diminutive crab shell through a reaction with calcium and phosphate precursors. A total of 36 male cavia cobaya guinea pigs underwent mandibular incisor extraction, divided into four groups: the chitosan powder from blue crab shells group, the chitosan gel and HA from blue crab shells group, the positive control given commercially available HA bone graft, and the negative control group given a placebo gel. On days 7, 14, and 21, sacrifices were performed to collect the mandibular jaw tissue of the cavia cobaya guinea pigs, and immunohistochemical examinations were conducted to determine BMP-2 expression. Data analysis was conducted using the Shapiro-Wilk test, ANOVA, and post hoc LSD test. Results: On days 7, 14, and 21, there was an increase in BMP-2 expression. Conclusion: Chitosan and hydroxyapatite derived from the shells of Portunus pelagicus have been demonstrated to effectively enhance BMP-2 expression.